HBT-based turn-on fluorescent probe for discrimination of homocysteine from glutathione/cysteine and its bioimaging applications. Issue 27 (14th March 2017) - Chen, Fengzao; Chen, Zhen; Sun, Yuanchao; Liu, Heng; Han, Deman; He, Hanping; Zhang, Xiuhua; Wang, Shengfu
Abstract : In this work, we firstly reported a new type of turn-on fluorescent probe HBTI for Hcy over GSH/Cys based on ESIPT and heavy atom effect strategy. Abstract : Based on ESIPT and heavy atom effect strategy, we firstly reported a new type of turn-on fluorescent probe for Hcy. This probe displayed fast response time (15 min), excellent selectivity over other interfering species and high sensitivity with a low detection limit of 1.6 × 10 −7 M in PBS buffer containing 1% CH3 CN (v/v). Moreover, the probe was also successfully applied for fluorescence imaging of Hcy in HeLa cells.